Developing capacity within the British civil service: the case of the Stabilisation Unit. Issue 8 (16th November 2020) - Connolly, John; Pyper, Robert
ABSTRACT: This paper examines the training and development dimensions of a relatively recent entity within the British civil service—the Stabilisation Unit (SU). Now accountable to UK National Security Council, the unit came into being in 2007 in order to co-ordinate work between the Foreign & Commonwealth Office, the Department for International Development, and the Ministry of Defence in the wake of military interventions in Iraq and Afghanistan. The unit now has a broad crisis prevention and response function. This paper shows how the unit has become an important training and capacity building feature of the modern British civil service. The concluding argument is that there is considerable potential for the unit to be an organizational agent for joining-up government as part of a renewed modernization agenda for civil service learning, training and development.